Confined Monolayer Ice Between CaF2 (111) and Graphene: Structure and Stability - Li, Shi-Qi; Qiu, Shi; Liu, Hongsheng; Chen, Maodu; Gao, Junfeng (Frontiers in Physics, 2021)
Water monolayer can form in layered confined systems. Here, CaF2(111) and graphene are chosen as modelling systems to explore the structure and stability of confined monolayer water. First, water molecules tend to intercalate into the confined space between graphene and CaF2, rather than on bare surface of graphene. Water molecules can move fast in the confined space due to low diffusion barrier. These water molecules are likely to aggregate together forming monolayer ice. Four ice phases including ice II, ice III, ice IV and ice Ih are compared in this confined system. Intriguingly, all the ice phases undergo very small deformation, indicating the 2D monolayer ice can be stable in CaF2-graphene confined system. Beyond, projected band structures are also plotted to understand electronic behavior of these confined ice phases. Nearly all the bands originated from confined ices are flat and locate about 2 3 eV below the Fermi level. Binding energy calculations suggest the stability sequence in this confined system are: Ih-up≈Ih-down≈II < IV < III. Our results bring new insights into the formation of water monolayer production in such a confined condition.